Preparation and identification novel angiotensin-converting enzyme-inhibitory peptides derived from fish waste - Pakdee Awadsaya; Roytrakul Sittiruk; Wonganu Benjamaporn (E3S Web of Conferences)
The purpose of the research is to compare short peptides from different hydrolysates of fish entrails that can inhibit the activity of angiotensin-converting enzyme (ACE). Fish hydrolysates derived from Catfish, Tilapia, and Mackerel entrails were digested by pepsin and passed through the 3kDa cutoff column. The fraction containing peptides shorter than and equal to 3kDa from catfish hydrolysate has the great ability to inhibit ACE activity in converting the substrate (Furanacroloy-Phe-Gly-Gly, FAPGG) and producing FAP and GG as the products of the reaction. The 3kDa filtrate from the catfish hydrolysate had activity like Captopril, a drug for treating hypertension. The 3kDa filtrate derived from the catfish entrail hydrolysate was purified using OFFGEL electrophoresis and then passed through the C18 column. The 3kDa filtrate was separated into two fractions and then these fractions were determined ACE inhibitory activity. The result showed that the fractions containing hydrophilic peptides and others containing hydrophobic peptides possessed inhibitory activity against ACE. Those fractions were analyzed with LCMS/MS for sequencing. The results revealed that synthesized peptides; ASNLHGV, LFKDLR, PGYALQR, and LETAKSR, derived from the catfish hydrolysate showed anti-ACE activity against its substrate.